Peran Otoritas Jasa Keuangan dan Lembaga Penjamin Simpanan dalam Menjaga Stabilitas dan Keamanan Sistem Keuangan - Niharotul Faizah; Dewi Ratih; Kamelia Elima'ana Mafudloh; Muhammad Tufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
The Financial Services Authority (OJK) is an institution that is independent and free from interference from other parties that has the functions, duties, and authority to regulate, supervise, examine, and investigate as referred to in Law No. 21 of 2011 concerning OJK. The establishment of this banking financial services sector supervisory institution was established in accordance with the mandate of Law Number 3 of 2004 concerning amendments to Law Number 23 of 1999 concerning Bank Indonesia. This research uses the literature review method. This research combines various sources of literary information, namely books, scientific journals, newspapers, the internet, and theses related to the topic, namely